Cathodic mass transfer relationship of carbonic acid solutions with trace dissolved oxygen contamination - John, D; Kinsella, B; Bailey, S; De Marco, R (Curran Associates Inc., 2008)
Cathodic polarisation curves of carbon steel in carbonic acid solutions typically exhibit a limiting current behaviour that has been associated with the rate of mass transfer. In studies using the jet impingement technique, the magnitude of this limiting current behaviour has been found to be strongly affected by the presence of trace dissolved oxygen. This paper presents a theoretical assessment of the mass transfer limited cathodic current to illustrate the pronounced effect of dissolved oxygen contamination <12 ppb. Discussion is presented regarding the implications of dissolved oxygen contamination on the interpretation of the mechanism of carbon dioxide corrosion. © 2009 by NACE International.